Obstetric Cholestasis: An Overview - Darshandhari Kapali, Gayatri (Journal of Nursing Education of Nepal, 2023)
Obstetric cholestasis is a multifactorial condition of pregnancy characterized by intense pruritus in the absence of a skin rash with abnormal liver function tests which is resolved after birth. It occurs during third trimester of pregnancy and incidence varies in different countries. Diagnostic findings usually have raised concentrations of bile acids greater than 10 micromoles /L and 40 micromoles/L have been associated with increased fetal risk. UDCA (Ursodeoxycholic acid) are beneficial for symptomatic relief of pruritus and decrease in abnormal liver function test and bile acid. In addition, detailed study of the consequences of maternal cholestasis on both placental transport function and fetal hepatic transport capacity may help to prevent fetal distress and Intra Uterine fetal Death in the clinical setting. Adverse perinatal outcome is a major concern with potential fetal risks, which may include spontaneous preterm birth, iatrogenic preterm birth and fetal death. The objective of the review is to explore and share about Obstetric cholestasis and its management.Fetal risk, Obstetric cholestasis, Pruritus
Keywords: Fetal risk; Obstetric cholestasis; Pruritus